Publishing Trends, Motivations, and Obstacles Among Pediatric Surgeons: An International Survey on Research Dissemination and Peer Review Challenges - Aubert, Ophelia; Gazzaneo, Marta; Moreno-Alfonso, Julio César; Ulman, Hilmican; Garnier, Hanna; Ure, Benno; Lacher, Martin (European Journal of Pediatric Surgery, 2025)
Objective This study aims to assess publishing trends, motivations, preferences, and challenges among pediatric surgeons globally.Methods A cross-sectional survey was conducted among pediatric surgeons from multiple countries, distributed through the Trainees of European Pediatric Surgery (TEPS) network and social media. The anonymous questionnaire contained 26 items focusing on journal preferences, motivations for publishing, obstacles faced, peer-review experiences, open access publishing, and methods of research dissemination.Results A total of 172 responses were collected from pediatric surgeons in 33 countries. Most respondents worked in tertiary hospitals (88%) and were consultants or senior attendings (49%). Over half (65%) had published at least one scientific paper in the last 3 years. PubMed was the primary search engine (82%), and pediatric surgical journals were the preferred outlets for publication (87%). Key motivations for choosing a journal were impact factor (22%) and scope (19%), while publication costs (38%) and slow review processes (22%) were the primary deterrents. Open access publication options were used by more than half of respondents, with a third spending less than €2,500 on fees. Social media, particularly Instagram, emerged as a popular platform for research dissemination.Conclusion Pediatric surgeons prefer publishing in specialized journals, with impact factor and scope being key drivers of journal choice. Publication costs and the peer-review process are the most significant obstacles. Efforts to address these challenges, such as reducing fees and enhancing the review process, are crucial for facilitating research dissemination in pediatric surgery.
Keywords: global publishing trends; research dissemination; peer-review; publication barriers